Answer :

x(x + 9)(x + 3)(x + 6) + 56


= (x2 + 9x) (x2 + 6x + 3x + 18) + 56


= (x2 + 9x) (x2 + 9x + 18) + 56


Let x2 + 9x = a


= a (a + 18) + 56


= a2 + 18a + 56


= a2 + 14a + 4a + 56


=a(a + 14) + 4(a + 14)


= (a + 4)(a + 14)


Put back the values to get,


= (x2 + 9x + 4)( x2 + 9x + 14)


= (x2 + 9x + 4)( x2 + 7x + 2x + 14)


= (x2 + 9x + 4)[( x(x + 7) + 2(x + 7)]


= (x2 + 9x + 4)(x + 2)(x + 7)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

I/we factorise thWest Bengal - Mathematics

I/we factorise thWest Bengal - Mathematics

I/we factorise thWest Bengal - Mathematics

I/we factorise thWest Bengal - Mathematics

Let’s resolve intWest Bengal - Mathematics

Let’s resolve theWest Bengal - Mathematics

Let’s resolve theWest Bengal - Mathematics

Let’s resolve intWest Bengal - Mathematics

Let’s resolve intWest Bengal - Mathematics

Let’s resolve intWest Bengal - Mathematics